2010
DOI: 10.3340/jkns.2010.48.2.162
|View full text |Cite
|
Sign up to set email alerts
|

Two Separate Episodes of Intramedullary Spinal Cord Metastasis in a Single Patient with Breast Cancer

Abstract: J Korean Neurosurg Soc 48 : [162][163][164][165] 2010 Intramedullary spinal cord metastases are very rare. Patients with breast cancer as the primary source of intramedullary spinal cord metastases tend to do better than other types of cancer. We report the very unusual case of a woman with breast cancer who had two separate episodes of intramedullary spinal cord metastasis. KEY WORDS :Intramedullary˙ Cervical˙ Thoracolumbar˙ Metastases˙ Breast cancer˙ Surgical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…In our literature review, we found only one case report about a surgically treated double intramedullary metastasis in patient suffering from breast cancer, but the repetitive lesions occurred separately, each of which as a solitary lesion [36]. In contrast, we reported the treatment of two different intramedullary metastases occurring at the same time.…”
Section: Discussionmentioning
confidence: 94%
“…In our literature review, we found only one case report about a surgically treated double intramedullary metastasis in patient suffering from breast cancer, but the repetitive lesions occurred separately, each of which as a solitary lesion [36]. In contrast, we reported the treatment of two different intramedullary metastases occurring at the same time.…”
Section: Discussionmentioning
confidence: 94%
“…These modalities do not pass through the blood-spinal cord barrier. Chemotherapy has no further effect on survival [ 7 , 17 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some authors have proposed the possibility that chemotherapy for intracerebral metastases can cross the disrupted blood-brain barrier and extrapolated this to ISCMs [ 17 19 ]. When compared, the blood-brain barrier and the blood-spinal cord barrier are not entirely identical.…”
Section: Discussionmentioning
confidence: 99%
“…Early surgical intervention is necessary for preventing neurological deterioration and improving the quality of life [ 9 ]. Adjuvant radiotherapy should be given especially in cases of partial resection [ 10 ]. In the review article, written by Rostami et al in 2013, the number of MISC cases with the only primary cancer being breast cancer is given as 85.…”
Section: Discussionmentioning
confidence: 99%